Fred the firefighter - Brooks, Felicity; Litchfield, Jo (London : Usborne ; Tulsa, Okla. : EDC, 2006)
Fred the firefighter and his crew respond to a house fire on Randolph Avenue.
3.1
K-3
Keywords: Fire fighters -- Fiction; Fire extinction -- Fiction